The Impact Of E-Commerce Development On The Implementation Of Consumer Protection Law In Trade Law In Indonesia - Muhammad Annas Ferdhiyanto; Mohammad Yaasiin TW; Dewa Pamungkas; Diky Dikrurahman; Deni Yusup Permana (International Journal Labs, 2025)
The development of information and communication technology has brought major changes in various aspects of life, including in the field of trade. E-commerce or electronic commerce has become one of the sectors that is growing rapidly in Indonesia. However, on the other hand, the development of e-commerce also raises various new challenges in consumer protection. This research aims to analyze the impact of e-commerce developments on the application of consumer protection laws in trade law in Indonesia. This research uses normative juridical research methods. The data collection technique used in this research is literature study. The collected data was analyzed using qualitative analysis methods. The research results show that the development of e-commerce in Indonesia has had a significant impact on the implementation of consumer protection laws. Some of the main problems faced by consumers include non-transparency of product information, fraud, and a lack of effective dispute resolution mechanisms. Although there are various regulations governing consumer protection, their implementation still needs to be improved, especially in the context of e-commerce. This research recommends increasing outreach and education regarding consumer rights, strengthening regulations specific to e-commerce, and developing dispute resolution mechanisms that are more effective and easily accessible to consumers.